Cannabinoid modulation of limbic forebrain noradrenergic circuitry - Carvalho, Ana Raquel Franky Gomes (2010)
Both the endocannabinoid and noradrenergic systems have been implicated in neuropsychiatric disorders. Importantly, low levels of norepinephrine are seen in patients with depression, and antagonism of the cannabinoid receptor type 1 (CB1R) is able to induce depressive symptoms in rodents and humans. Whether the interaction between the two systems is important for the regulation of these behaviors is not known. In the present study, adult male Sprague-Dawley rats were acutely or chronically administered the CB1R synthetic agonist WIN 55,212-2, and alpha2A and beta1 adrenergic receptors (AR) were quantified by Western blot. These AR have been shown to be altered in a number of psychiatric disorders and following antidepressant treatment. CB1R agonist treatment induced a differential decrease in alpha2A- and beta1-ARs in the nucleus accumbens (Acb). Moreover, to assess long-lasting changes induced by CB1R activation, some of the chronically treated rats were killed 7 days following the last injection. This revealed a persistent effect on alpha2A-AR levels. Furthermore, the localization of CB1R with respect to noradrenergic profiles was assessed in the Acb and in the nucleus of the solitary tract (NTS). Our results show a significant topographic distribution of CB1R and dopamine beta hydroxylase immunoreactivities (ir) in the Acb, with higher co-localization observed in the NTS. In the Acb, CB1R-ir was found in terminals forming either symmetric or asymmetric synapses. These results suggest that cannabinoids may modulate noradrenergic signaling in the Acb, directly by acting on noradrenergic neurons in the NTS or indirectly by modulating inhibitory and excitatory input in the Acb.